Protein interactions in the herpes simplex virus type 1 VP16-induced complex: VP16 peptide inhibition and mutational analysis of host cell factor requirements. - Simmen, K A (1997)
The herpes simplex virus VP16 protein functions as a potent transcriptional activator and targets DNA sites with the consensus TAATGARAT present in all the viral immediate-early gene promoters. To do so, VP16 directs assembly of a multiprotein complex involving two cellular proteins, host cell factor (HCF) and the Oct-1 DNA-binding transcription factor. To investigate the importance of specific protein-protein interactions to formation of this VP16-induced complex (VIC), we used oligopeptides to prevent VIC assembly. Linear and cyclic peptides corresponding to a region of VP16 previously implicated in complex formation were potent inhibitors of VIC assembly. To further characterize the protein interactions involved, we cloned a human cDNA encoding the minimal VP16 interaction domain of HCF, containing amino acids 1 to 380 [HCF (1-380)]. The REHAYS-based peptides active in preventing VIC assembly were found to specifically block binding of VP16 to HCF (1-380), without affecting VP16-Oct-1 binding. The inhibitory activity of these VP16 peptides was strictly sequence specific for the EHAY residues. Site-directed mutagenesis of the HCF (1-380) domain revealed residues E102 and K105 to be critical determinants in support of VIC formation. Alteration of a single residue in HCF, K105, was shown to virtually abolish complex assembly. Interestingly however, none of the HCF mutants that were impaired in their ability to support complex formation exhibited defects in direct VP16 binding, supporting loss of function at a higher order in complex assembly.